MKitchen IIUM students integrate food with budi sejahtera - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohamad Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; et al. (mKitchen Kulliyyah of Information and Communication Technology (KICT), 2022)
This book explains mKitchen IIUM students’ journey in mKitchen by integrating food entrepreneurship with Budi Sejahtera. The students started the journey with in-class training on entrepreneurship, business plan development, digital marketing, and cash management. Then, the students had a cooking demonstration on Turkish delights. One month has been allocated for both process and content phases of training. Then, the students had the pre-internship demonstration at Wadi Budi IIUM before a month-long internship during Ramadan 1443.